MnPS3 spin-flop transition-induced anomalous Hall effect in graphite flake via van der Waals proximity coupling. Issue 45 (18th November 2020) - Zhang, Ying; Wang, Wenhui; Huang, Meng; Liu, Ping; Hu, Guojing; Feng, Chao; Lei, Xueyan; Gu, Meng; Yang, Hongxin; Liu, Kaihui; Xiang, Bin; Lu, Yalin
Abstract : Detection of the antiferromagnetic (AFM) state is an important issue for the application of two-dimensional (2D) antiferromagnets in spintronics, and interfacial exchange coupling is a highly efficient means to detect AFM order. Abstract : Detection of the antiferromagnetic (AFM) state is an important issue for the application of two-dimensional (2D) antiferromagnets in spintronics, and interfacial exchange coupling is a highly efficient means to detect AFM order. However, there are no experimental reports of AFM state detection in van der Waals heterostructures, based on which 2D AFM spintronics can be developed. In this paper, we report a spin flop transition (SFT)-induced anomalous Hall effect in a heterostructure of MnPS3 /graphite flake (GF) through van der Waals proximity coupling. The scaling behavior study and theoretical calculations confirm that the SFT in AFM MnPS3 can generate momentum-space nonzero Berry curvature integration in the adjacent GF. Our work opens a path for the realization of AFM state detection through the proximity effect in a stacking structure, thereby promoting the application of 2D antiferromagnets in future 2D spintronics.